Peran work engagement dalam memediasi pengaruh work environment dan work-life balance terhadap turnover intention tenaga ahli anggota DPR RI - Eka Fitri Suryani; Yanuar Yanuar (Universitas Tarumanagara, 2026)
This study examines the influence of work environment and work-life balance on turnover intention among expert staff members of the Indonesian House of Representatives (DPR RI), with work engagement as a mediating variable. The turnover intention construct used in this study includes indicators reflecting the tendency to stay (retention); therefore, higher TI scores indicate a stronger intention to remain in the organization. A quantitative causal cross-sectional design was employed, involving 215 expert staff respondents, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings reveal that both work environment and work-life balance significantly enhance employees’ tendency to stay, which substantively reduces turnover intention. Work environment demonstrates the strongest effect on work engagement, indicating that supervisory support, clarity of roles, and a supportive work climate function as critical job resources within the high-pressure political environment of DPR RI. Work engagement also significantly affects turnover intention and mediates the relationship between work environment and turnover intention. These results align with the motivational mechanism of the Job Demands–Resources (JD-R) Theory, suggesting that job resources strengthen engagement and ultimately reduce employees’ intention to leave. Theoretically, this study contributes to the limited body of research on work behavior in public–political sectors. Practically, it highlights the importance of improving the work environment, implementing flexible work-life balance policies, and developing engagement-enhancing programs to strengthen the retention of expert staff at DPR RI. Penelitian ini bertujuan untuk menganalisis pengaruh work environment dan work-life balance terhadap turnover intention tenaga ahli anggota DPR RI, dengan work engagement sebagai variabel mediasi. Konstruk turnover intention dalam penelitian ini memuat indikator yang mencerminkan kecenderungan bertahan (retention), sehingga peningkatan skor TI menunjukkan meningkatnya keinginan untuk tetap bekerja. Pendekatan kuantitatif dengan desain kausal cross-sectional digunakan pada 215 responden tenaga ahli, dan data dianalisis menggunakan Partial Least Squares–Structural Equation Modeling (PLS-SEM) melalui SmartPLS 4.0. Hasil penelitian menunjukkan bahwa work environment dan work-life balance secara signifikan meningkatkan kecenderungan bertahan tenaga ahli, yang secara substantif menurunkan turnover intention. Work environment memiliki pengaruh paling kuat terhadap work engagement, menegaskan bahwa dukungan atasan, kejelasan peran, dan iklim kerja yang kondusif merupakan job resources penting dalam konteks kerja legislatif. Work engagement juga berpengaruh signifikan terhadap turnover intention dan terbukti memediasi hubungan antara work environment dan turnover intention. Temuan ini konsisten dengan mekanisme motivasional dalam Job Demands–Resources (JD-R) Theory, di mana job resources meningkatkan engagement dan pada akhirnya menekan niat keluar. Secara teoretis, penelitian ini memperkaya kajian perilaku kerja di sektor publik-politik yang masih terbatas diteliti. Secara praktis, penelitian ini menekankan perlunya perbaikan lingkungan kerja, kebijakan work-life balance yang lebih fleksibel, serta program pengembangan engagement untuk meningkatkan retensi tenaga ahli DPR RI.